Shading Responses of the Seagrass, Halophila ovalis: A Prelimin - Bujang, Japar Sidik; Jamaludin, Mohammad Rozaimi; Kusnan, Misri; Omar, Hishammuddin (Malaysian Journal of Science, 2005)
The seagrass, Halophila ovalis was grown in culture to investigate its responses to artificial shading. H. ovalis was collected from a low water level seabed off Teluk Kemang coast (2°, 30'N, 101°, 45'E) in Negeri Sembilan, Malaysia. Live plant portions were transplanted indoors providing natural sunlight, substrate and seawater. Shade screens providing 10-15 percent of incident light, resulting in approximately 150-250 μ mol mˉ² s ˉˡ of light intensity, was imposed. Observations after three months revealed morphological responses of the plant towards both indoor culturing as well as towards shading Plants in cultures exhibited two leaf size variations- both larger and smaller leaf sizes. In comparison, H. ovalis in the wild showed little variations in leaf size. As such, this study can provide insights to the plant's responses to photoacclimational conditions as well as to culturing conditions.